2008
DOI: 10.1111/j.1582-4934.2008.00266.x
|View full text |Cite
|
Sign up to set email alerts
|

MAPK/ERK signalling mediates VEGF‐induced bone marrow stem cell differentiation into endothelial cell

Abstract: Multi-potent adult progenitor cells (MAPCs) differentiate into endothelial cells (ECs) in the presence of vascular endothelial growth factor (VEGF). The mechanism(s) of VEGF-induced differentiation of MAPCs to ECs are not yet known. We, therefore, examined the role of mitogen-activated protein kinase/extracellular signal-regulated kinase (p42/44-MAPK/ERK1/2) signalling in endothelial differentiation from bone marrow stem cells. We observed that VEGF stimulation of MAPCs for 14 days results in a significant exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
107
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(120 citation statements)
references
References 58 publications
11
107
0
2
Order By: Relevance
“…In this study, we observed that a sustained activation of the ERK1/2 is required for endothelial-like differentiation of iDCs. It is established that the nuclear translocation of phosphorylated ERK is key to the differentiation of various cells (14,15,30). our results demonstrated that activated ERK1/2 was present in the nucleus of cells incubated with SW620 supernatant.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…In this study, we observed that a sustained activation of the ERK1/2 is required for endothelial-like differentiation of iDCs. It is established that the nuclear translocation of phosphorylated ERK is key to the differentiation of various cells (14,15,30). our results demonstrated that activated ERK1/2 was present in the nucleus of cells incubated with SW620 supernatant.…”
Section: Discussionsupporting
confidence: 55%
“…The ERK1/2 signaling plays a key role in mediating signals from membrane receptors to the nucleus, and is involved in the processes of cell growth, differentiation, proliferation and apoptosis (28,29). A study has shown that the ERK pathway plays a central role in VEGF-induced bone marrow stem cell differentiation into ECs (15). In this study, we observed that a sustained activation of the ERK1/2 is required for endothelial-like differentiation of iDCs.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Subsequently, PI3K activation activates PKC, which is followed by the activation of MAPKKK and MAPK pathway-signalling molecules (Rask-Madsen & King 2008). Most researchers believed that VEGF induces phosphorylation of Ras-GTP in endothelial cells, and that activated Ras activates Raf-MEK-ERK, which is a signalling pathway required by in vitro cultured HUVEC during the migration, proliferation and formation of new blood vessels (the Ras Raf MEK ERK-activated MAPK pathway) (Xu et al 2008). Other investigators believe that after binding VEGF and VEGFR-2, MAPK signal transduction is activated through the PLC-g PKC pathway (Grothey & Ellis 2008).…”
Section: Discussionmentioning
confidence: 99%
“…6,7,28 Potential candidates include hepatocyte growth factor, epidermal growth factor, oncostatin M, and vascular endothelial growth factor, and these factors were therefore nominated as modulators of stem cell differentiation. 5,[29][30][31] However, the length of time required during hepatic differentiation of MSCs under prolonged exposure in the specific culture media is the major drawback. On average, the expression of hepatic-specific genes in MSCs were detectable by culturing in growth factor-enriched medium for more than 1 week.…”
Section: Discussionmentioning
confidence: 99%